Pengaruh Variasi Konsentrasi Metanol dan Biogasoline Hasil Pirolisis Terhadap Performa Mesin Otto dengan Menggunakan Dynotest - Siahaan, Enzo W.B; Sidabutar, Rotama Arifin; Sitanggang, Hodmiantua (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
Global environmental issues are becoming more pressing with the increasing volume of plastic waste and the decline in fossil fuel resources. According to a report from the United Nations Environment Programme (UNEP), more than 300 million tons of plastic are produced annually, and around 50% of it is single-use plastic. This study aims to evaluate the effect of adding methanol to biogasoline from pyrolysis of plastic waste on an Otto engine, in this case a carburetor motorcycle. Plastic waste processed through pyrolysis produces biogasoline, which is then mixed with methanol in concentrations of 20% (BM20) and 30% (BM30). This test was carried out using a dynotest machine to measure power, torque, and air fuel ratio (AFR) in the engine speed range of 1000 to 7500 rpm. The results showed that the addition of methanol had an effect on increasing engine performance, especially on the power and torque produced. At 20% methanol concentration, engine power increased up to 5500 rpm before decreasing at 7500 rpm, while at 30% concentration, power increased from 200 rpm and began to decrease at 6700 rpm. Meanwhile, AFR showed a stable tendency at the beginning of engine speed with a significant decrease at high speed, especially in BM30. For AFR, BM30 produced more stable combustion at low speed but experienced a drastic decrease at high speed, with the air-fuel ratio reaching an imbalance above 7000 rpm. This study contributes to the development of alternative fuels based on plastic waste that are more efficient and environmentally friendly. The addition of methanol has been shown to improve the combustion quality of biogasoline, although further optimization is needed to achieve consistent performance across all engine speed ranges.